THE URGENCY OF MAQĀŞID SHARĪA FOR HALAL TOURISM REGULATION IN INDONESIA - Nurjannah; Awalauddin, Murtiadi; K, Amiruddin; Fadel, Muhammad; Asti, Mulham Jaki (Al-Risalah Jurnal Ilmu Syariah dan Hukum, 2023)
Halal tourism is one of the halal value chains that has experienced very significant development, not only in Muslim-majority countries but has penetrated into minority countries. Indonesia is also one of the drivers of halal tourism with various achievements achieved in the international arena, however, the regulation of halal tourism is still a polemic and there is no strong legal umbrella governing it. This research aims to see the urgency of maqashid sharia on halal tourism regulation in Indonesia. This research is a normative research with literature search method. Data obtained from journals, books, research relevant to the discussion are reviewed descriptively. The result of the research is that related to halal tourism in Indonesia there has been a MUI fatwa No. 18/MUI-DSN/X/2016 concerning Guidelines for the Implementation of Tourism Based on Sharia Principles and various other laws and regulations, but it has not fully given effect to tourism management and development, especially legal certainty. So in making regulations, the elements of maqashid sharia are needed, namely protecting religion, soul, mind, offspring and property which is the basic foundation because it is in line with the purpose of establishing halal tourism, namely the realization of maslahah and avoiding mafsadah which can be achieved by all related elements.